2012
DOI: 10.1128/aem.08018-11
|View full text |Cite
|
Sign up to set email alerts
|

Soil Fungal Cellobiohydrolase I Gene ( cbhI ) Composition and Expression in a Loblolly Pine Plantation under Conditions of Elevated Atmospheric CO 2 and Nitrogen Fertilization

Abstract: The simultaneous increase of atmospheric CO 2 and nitrogen (N) deposition to terrestrial ecosystems is predicted to alter plant productivity and, consequently, to change the amount and quality of above-and belowground carbon entering forest soils. It is not known how such changes will impact the composition and function of soil fungal communities that play a key role in degrading complex carbon. We sequenced the fungal cellobiohydrolase I gene (cbhI) from soil DNA and cDNA to compare the richness and compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…() found decreased abundance of functional markers associated with both cellulose and lignin degradation in response to nitrogen, and a study which targeted both DNA and RNA found no response of cbhI to nitrogen (Weber et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…() found decreased abundance of functional markers associated with both cellulose and lignin degradation in response to nitrogen, and a study which targeted both DNA and RNA found no response of cbhI to nitrogen (Weber et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Based on the LSU, N addition increased fungal community richness, reduced the relative abundance of Basidiomycota fungi, and altered community composition, consistent with the present study. Weber et al (2012) provided evidence that the richness and composition of the cellulolytic fungi surveyed in this study were distinct in both DNA-and cDNA-based gene surveys and were dominated by Basidiomycota that have low or no representation in public databases. The surveys did not detect differences in richness or phylum-level composition of cbhI-containing, cellulolytic fungi that correlated with elevated CO 2 or N fertilization at the time of sampling (Entwistle et al 2013).…”
Section: Soil Acidification and Increasing Phmentioning
confidence: 80%
“…Probably these are a relic of the supply of substrates, but as this is not measured here, we can only speculate. Earlier studies have found that GH7 composition or richness in soil or litter is not significantly affected by tree species (Edwards et al, 2008), genetic modification of potato leaves (Hannula et al, 2013), elevated CO 2 (Hassett et al, 2009), or N fertilization (Weber et al, 2012). Our results corroborate the lack of differentiation power of the GH7 gene to environmental disturbances.…”
Section: Discussionmentioning
confidence: 98%